EFEKTIVITAS AZOLLA MICROPHYLLA DAN EICHHORNIA CRASSIPES DALAM PENGOLAHAN LIMBAH CAIR TAHU - Rahman, Aldo; Lisha, Sri Yanti; Fitrada, Wathri (Universitas Jambi, 2024)
The Indonesian tofu industry is dominated by small scale industries with limited capital, so most do not have waste treatment facilities. Waste from the tofu industry in the form of liquid waste has a high BOD and COD content, and exceeds the quality standards set by PerMenLHK No. P.21 of 2018. Treatment of liquid waste from the tofu industry is necessary to reduce BOD and COD concentrations. Phytoremediation is an effective, efficient and environmentally friendly liquid waste treatment method to reduce BOD and COD parameters. This research aimed to determine the effectiveness of Azolla microphylla and Eichhornia crassipes in reducing BOD and COD of tofu liquid waste. The research data consists of BOD and COD test results following the phytoremediation method with a contact time of 15 days. Initial testing of tofu liquid waste showed BOD and COD results of 193.5 mg/L and 489.2 mg/L, respectively. After the tofu liquid waste was treated with the phytoremediation method, the BOD and COD reduction efficiencies were 48.27% and 74.52%, respectively. The effective weight combination for the reduction of BOD and COD parameters is 100 Azolla microphylla + 300 Eichhornia crassipes.